The Effect of MST 1 Inhibition through Hippo Pathway on Diabetes Mellitus (DM) Induced Osteoporosis - Kintan Adelia Farahannisa; Gadis Meinar Sari; Heri Suroto (Indonesian Andrology and Biomedical Journal, 2022)
Osteoporosis is a chronic metabolic disorder of the musculoskeletal system associated with reduced bone strength. One of the causes of secondary osteoporosis is diabetes mellitus (DM). The prevalence of both disorders keeps increasing with time. Therefore, this review is conducted to find a possible solution to prevent DM-induced osteoporosis. Diabetes mellitus mainly affects the bone through glucose uptake during the bone remodeling process. Glucose uptake through GLUT 1 is regulated by MST 1, which is an upstream kinase of the Hippo signaling pathway. MST 1 is responsible for regulating cell growth, proliferation, and apoptosis. In the bone remodeling process, MST 1 plays a role by regulating actin ring structures and the integrin signaling pathway. Moreover, DM is also associated with increased oxidative stress. Increased oxidative stress will activate Hippo signaling pathway. This will trigger cellular apoptosis as the Hippo signaling pathway plays a role mainly as a tumor suppressor. Increased cellular apoptosis will cause an imbalance in the bone remodeling process, disrupting bone quality. Inhibition of MST 1 through the Hippo signaling pathway will increase cell growth and reduce cellular apoptosis. Increased cell growth might increase osteogenesis during the bone remodeling process, thus resulting in better bone quality in DM-induced osteoporosis.